Morphological and molecular identification of ticks collected from dogs (Canis lupus familiaris) with ehrlichiosis in Chiclayo, Peru - Cervantes S., Miguel; Masgo C., Deysi; Ramírez V., Leyla; Álvarez M., Grecia; Li E., Olga; Vásquez-Ydrogo., Alvaro; Gomez-Puerta, Luis A.; Hoyos S., Luis (Revista de Investigaciones Veterinarias del Perú, 2020)
The present study aimed to identify morphologically and molecularly the ticks of dogs with ehrlichiosis in the Chiclayo district (Lambayeque, Peru). A total of 297 ticks from 74 dogs were collected and morphologically identified as Rhipicephalus sanguineus s.l. Nine specimens were used for molecular identification using the 16S rDNA ribosomal gene. The sequences obtained were aligned with sequences of R. sanguineus s.l. from Brazil and Colombia (Northern Lineage), Argentina, Chile and Uruguay (Southern Lineage), Spain, Italy and South Africa, showing a genetic divergence of 0-0.3% and 6.1-6.8% with the Northern Lineage and Southern Lineage, respectively. The phylogenetic analysis grouped the sequences of Peru with those of the Northern Lineage and South Africa, segregating them from the sequences of the Southern Lineage and Europe. The results show that R. sanguineus s.l. from Chiclayo, Peru, belongs to the Northern Lineage. El presente estudio tuvo como objetivo identificar morfológica y molecularmente las garrapatas de perros con ehrlichiosis en el distrito de Chiclayo (Lambayeque, Perú). Se colectaron 297 garrapatas de 74 perros y fueron identificadas morfológicamente como Rhipicephalus sanguineus s.l. Nueve especímenes fueron utilizados para la identificación molecular usando el gen ribosomal 16S rADN. Las secuencias obtenidas fueron alineadas con secuencias de R. sanguineus s.l de Brasil y Colombia (Linaje del Norte), Argentina, Chile y Uruguay (Linaje del Sur), España, Italia y Sudáfrica, mostrando una divergencia genética de 0-0.3% y 6.1-6.8% con el Linaje del Norte y Linaje del Sur, respectivamente. El análisis filogenético agrupó las secuencias del Perú con las del Linaje del Norte y Sudáfrica, segregándolas de las secuencias del Linaje del Sur y Europa. Los resultados demuestran que R. sanguineus s.l de Chiclayo, Perú, pertenece al Linaje del Norte.